Meeting the universe halfway : quantum physics and the entanglement of matter and meaning - Barad, Karen Michelle (e-Duke books scholarly collection., 2007)
"Meeting the Universe Halfway is an ambitious book with far-reaching implications for numerous fields in the natural sciences, social sciences, and humanities. In this volume, Karen Barad, theoretical physicist and feminist theorist, elaborates her theory of agential realism. Offering an account of the world as a whole rather than as composed of separate natural and social realms, agential realism is at once a new epistemology, ontology, and ethics. The starting point for Barad's analysis is the philosophical framework of quantum physicist Niels Bohr. Barad extends and partially revises Bohr's philosophical views in light of current scholarship in physics, science studies, and the philosophy of science as well as feminist, poststructuralist, and other critical social theories. In the process, she significantly reworks understandings of space, time, matter, causality, agency, subjectivity, and objectivity."--Publisher's description.